Movement application for a positive well-concept among the educable mentally retarded lower primary level - Inoturan, Rebecca P. (1973)
The purpose of the study is to prove the contention that classroom demonstrations on movement exploration for normal pupils can also be applicable to educable mentally retarded children. It seeks to describe movement exploration and how it can be taught to the educable mentally retarded, the needs of the educable mentally retarded that can be satisfied in movement exploration, and the movement exploration activities that can be taught to the educable mentally retarded in the lower primary level.
Thesis (Master of Arts in Teaching - Special Education : Mental Retardation Sequence)--University of the Philippines, Diliman.
Keywords: Self-perception in children -- Philippines; Children with mental disabilites -- Education (Primary) -- Philippines